2015
DOI: 10.1097/dss.0000000000000267
|View full text |Cite
|
Sign up to set email alerts
|

Patient Seeking Behaviors and Online Personas

Abstract: Social media can improve patient education, collaboration, recruitment, and online professional image, leading to healthier patient-centered care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(24 citation statements)
references
References 19 publications
(18 reference statements)
2
22
0
Order By: Relevance
“…The higher percentage of use found in our study may reflect the increased popularity of social media in health care, due to technological advances and recent changes in the public perception of social media [50]. Our findings support the argument that there has been a desire among patients to use social media as an additional medium to traditional platforms for obtaining medical information [48]. Thus, social networking sites can be utilized as a platform to distribute educational information regarding dermatological issues for a wider reach of the population and at a potentially lower cost, especially in resource-poor settings in developing countries [51,52].…”
Section: Principal Findingssupporting
confidence: 77%
See 1 more Smart Citation
“…The higher percentage of use found in our study may reflect the increased popularity of social media in health care, due to technological advances and recent changes in the public perception of social media [50]. Our findings support the argument that there has been a desire among patients to use social media as an additional medium to traditional platforms for obtaining medical information [48]. Thus, social networking sites can be utilized as a platform to distribute educational information regarding dermatological issues for a wider reach of the population and at a potentially lower cost, especially in resource-poor settings in developing countries [51,52].…”
Section: Principal Findingssupporting
confidence: 77%
“…Previous studies have documented the modest use of social media to find or share health-related content and particularly dermatology-related information. Despite reportedly high general social media engagement (85.0-99.3% of the participants reported regular access of at least one social media platform), only 19.0-31.7% of the participants reported accessing dermatology-related information [29,48]. We found that younger patients (aged 18-30 years) were significantly more likely to use social media.…”
Section: Principal Findingsmentioning
confidence: 55%
“…In response, the subreddit rallied around building a skin positive community with the goal of showcasing imperfections and encouraging the reconstruction of a healthy self-image. Reflecting a prior study on online dermatologic communities, shared struggles appear to link the subreddit’s members together and strengthen communal bonds through mutual aid and support [ 17 ]. Of cross-posts from alternative social media platforms, the majority were from Twitter and Instagram, sites that are frequently used by dermatology-relevant groups [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Approximately two-thirds of patients surveyed at a dermatology clinic indicated that they would prefer to read education material written by a physician rather than a layperson on social media. 16 Therefore, collaboration between physicians and patient-centered social networking groups could be an opportunity for patient education.…”
Section: Discussionmentioning
confidence: 99%